Biobibliografia cronológica de Pierre Monbeig : (Período: 1929-1985) - Heliana Angotti Salgueiro (Unité Mixte de Recherche 8504 Géographie-cités, 2002)
This biobibliography of Pierre Monbeig (1908-1987) is the result of work in progress on the Monbeig Archives collection at the University of São Paolo (where he taught from 1935 to 1946), under the direction of Helian Angotti-Sagueiro. She presents a list of around 210 titles classed chronologically according to the different stages of P. Monbeig’s career.